Total Synthesis of Asparenydiol by Two Sonogashira Cross-Coupling Reactions Promoted by Supported Pd and Cu Catalysts - Casotti, Gianluca; Fusini, Graziano; Ferreri, Matteo; Pardini, Luca Fidia; Evangelisti, Claudio; Angelici, Gaetano; Carpita, Adriano (Synthesis, 2020)
Asparenydiol, which is an important natural compound with potential pharmacological activities, was synthesized through two Sonogashira cross-coupling reactions catalyzed by supported Pd and Cu catalysts and by a Mitsunobu etherification. The optimization of the Sonogashira couplings allowed the use of catalysts supported on different matrices with good results in terms of catalytic efficiency and yields.
Keywords: Asparenydiol; Sonogashira cross-coupling; Mitsunobu etherification; total synthesis; solid-supported palladium catalyst